Explaining Ultramassive Quiescent Galaxies at 3 < z < 5 in the Context of Their Environments - Christian Kragh Jespersen; Adam C. Carnall; Christopher C. Lovell (The Astrophysical Journal Letters, 2025)
The swift assembly of the earliest galaxies poses a significant challenge to our understanding of galaxy formation. Ultramassive quiescent galaxies at intermediate redshifts (3 <  z  < 5) currently present one of the most pressing problems for theoretical modeling, since very few mechanisms can be invoked to explain how such galaxies formed so early in the history of the Universe. Here, we exploit the fact that these galaxies all reside within significant overdensities to explain their masses. To this end, we construct a modified version of the Extreme Value Statistics (EVS) code, which takes into account galaxy environment by incorporating clustering in the calculation. With this new version of EVS, we find that ultramassive quiescent galaxies at 3 <  z  < 5 do not present as serious a tension with simple models of galaxy formation when the analysis of a given galaxy is conditioned on its environment.